Effectiveness of acid solutions as intermediate irrigants between sodium hypochlorite and chlorhexidine on radicular adhesive interface - Magro, Miriam Graziele [UNESP]; Lucas de Sousa Gomes Costa, Joatan; Oliveira Barros, Antonia Patricia [UNESP]; Reis Só, Marcus Vinicius; Escalante-Otárola, Wilfredo Gustavo; Kuga, Milton Carlos [UNESP] (My University, 2025)
Purpose: This study evaluated the effectiveness of 10 % citric acid or 1 % peracetic acid, and their effects on radicular adhesive interface, when used as intermediate irrigation protocol between 2.5 % sodium hypochlorite and 2 % chlorhexidine in comparison with isopropyl alcohol or saline solution. Materials and methods: One hundred and twenty root canals were chemical-mechanical prepared. The specimens were distributed in 6 groups (n = 20), according irrigation protocol: sodium hypochlorite and EDTA (SHS-EDT); sodium hypochlorite and chlorhexidine (SHS-CHX); sodium hypochlorite, saline solution and chlorhexidine (SAS-CHX); sodium hypochlorite, alcohol and chlorhexidine (IPA-CHX); sodium hypochlorite and citric acid and chlorhexidine (CIA-CHX); sodium hypochlorite, peracetic acid and chlorhexidine (PAA-CHX). Sixty specimens were submitted to scanning electron microscope analysis to residues incidence evaluation. Energy Dispersive X-Ray Spectroscopy analysis was performed only in radicular middle third. Sixty specimens were subjected endodontic obturation and slices were obtained in radicular thirds and submitted to push out bond strength and dentin tags extension evaluations. The data of residues incidence evaluation were submitted to Kruskal-Wallis/Dunn tests, while push-out bond strength and endodontic sealer dentin penetration data were submitted to ANOVA/Tukey tests. Results: In all root canal thirds, SHS-CHX and SAS-CHX showed the highest. In all root canal thirds, IPA-CHX, CIA-CHX, PAA-CHX and SHS-EDT showed higher push out bond strength values. In all root thirds, IPA-CHX, CIA-CHX and PAA-CHX showed the greatest dentin tags extension. Conclusion: Acids and isopropyl alcohol used as intermediate solution between sodium hypochlorite and chlorhexidine provides lower residues incidence and the highest bond strength values and tags extension.
Keywords: Bond strength; Chlorhexidine; Endodontics; Sodium hypochlorite